MANNOSE SENSITIVITY AND MANNOSE RESISTANT HAEMAGGLUTINATON BY ESCHERICHIA COLI STRAINS ISOLATED FROM DIARRHOEIC CALVES - Udaykar, Aniruddha; Sharda, Rakesh (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Sixty two strains of E. coli were isolated from 116 diarrhoeic fecal samples out of which 20 (32.25%) and 25 (40.32%) exhibited mannose sensitive haemagglutination (MSHA) and mannose resistant haemagglutination (MRHA), respectively. The MSHA strains belonged to the somatic group O13, O14, O28, O69, O88, O106, O116 and O132, whereas MRHA strains belonged to somatic group O3, O13, O14, O28, O88, O106, 0116. Four untypable strains also showed MRHA. Six different MRHA patterns were recorded.
Keywords: E; coli; Haemagglutination; MRHA; MSHA